Development of the hardness, three-point bending, and wear behavior of self-lubricating Cu-5Gr/Al2O3-Cr3C2 hybrid composites. (April 2023) - Şap, Serhat; Usca, Üsame Ali; Uzun, Mahir; Giasin, Khaled; Pimenov, Danil Yu
This research aims to assess the mechanical characteristics of high-performance copper composites made utilizing powder metallurgy. The composites were produced by adding reinforcement elements (Al2 O3 -Cr3 C2 ) at different rates (3-6–9 wt.%) into copper-graphite (Cu-5Gr) via hot pressing technique. The microstructure, hardness, three-point bending and wear performance were analysed. The results determined that hybrid reinforced composites exhibited higher density, hardness and bending strength compared to Cu-Gr composites. The highest hardness of 73.02 HB was found in the CG-4 (copper graphit-4) sample. The maximum bending stress of 151.06 MPa occurred in sample CG-2. In addition, it was observed that the wear resistance increased significantly with the addition of the hybrid reinforcements. The lowest specific wear rate of 7.961 × 10 −7  mm 3 /N.m occurred in sample CG-6. As a result, 15.92%, 58.16% and 83.21% improvements were achieved in hardness, bending strength and wear performance, respectively. The current work indicates that certain mechanical properties of copper can be improved via the powder metallurgy process and the addition of reinforcements which could expand the applications and use of this metal in different industries.